Development of the Rice Moth, Corcyra cephalonica (St.) on Different Grains - Osman, Noorma (1986)
The development of the rice moth, Corcyra ,cephalonica in millet, sorghum, corn, wheat, padi and milled rice, both as whole.kernels and coarsely ground media, was studied. The parameters observed were:- percentage adults that emerged, average development time from oviposition to adult emergence and the fresh body weight of females. In general, ground kernels of all grains were more satisfactory for rearing C. cephalonica compared to whole kernels. The best all-grain ground and whole kernel media were milled rice and millet, respectively.